VTA glutamatergic inputs to nucleus accumbens drive aversion by acting on GABAergic interneurons - Qi, Jia (Nat Neurosci, 2016)
The ventral tegmental area (VTA) is best known for its dopamine neurons, some of which project to nucleus accumbens (nAcc). However, the VTA also has glutamatergic neurons that project to nAcc. The function of the mesoaccumbens-glutamatergic pathway remains unknown. Here, we report that nAcc photoactivation of mesoaccumbens-glutamatergic fibers promotes aversion. Although we found that these mesoaccumbens-glutamate-fibers lack GABA, the aversion evoked by their photoactivation depends on glutamate and GABA receptor signaling, and not on dopamine receptor signaling. We found that mesoaccumbens-glutamatergic-fibers establish multiple asymmetric synapses on single parvalbumin-GABAergic interneurons, and that nAcc photoactivation of these fibers drives AMPA-mediated cellular firing of parvalbumin-GABAergic interneurons. These parvalbumin-GABAergic-interneurons, in turn, inhibit nAcc medium spiny output neurons, as such, controlling inhibitory neurotransmission within nAcc. The mesoaccumbens-glutamatergic pathway is the first glutamatergic input to nAcc shown to mediate aversion, instead of reward, and the first pathway shown to establish excitatory synapses on nAcc parvalbumin-GABAergic interneurons.